Aktualisasi Diri dalam Komunitas: Studi Fenomenologis pada Mahasiswa Aktif di Organisasi Majelis Bahasa - Amalia Zahra Juliwanda; Dian Nurul Laili; Aulia Intan Lutfiyana; Safira Nurul Isna; Hikmah Anas (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the experiences of active students in the Language Council organization as a forum for developing their potential, identity, and interpersonal skills. A phenomenological qualitative approach was used with eight subjects selected through purposive sampling based on the criteria of active involvement for at least one semester and verbal ability in conveying experiences. Data were collected through semi-structured in-depth interviews, analyzed by identifying meaningful statements, coding, grouping themes, and formulating the essence of the experience. The results showed that the initial motivation for students to join was multidimensional, including academic, social, and personal needs, which influenced patterns of participation and adaptation within the organization. Students faced interpersonal, leadership, administrative, and internal challenges that encouraged the development of managerial skills, psychological resilience, and self-reflection. Social support from friends, seniors, and core administrators played an important role in strengthening self-confidence and active involvement, while also reinforcing positive experiences within the organization. The overall findings confirm that involvement in value- and language-based communities is an important mechanism for students to actualize themselves, shape their identities, and improve their personal and professional capacities.